Technostress Creators and Job Performance Among Frontliners: Theorizing the Moderating Role of Self-Efficacy - Saidy, Jeannette; Garanti, Zanete; Sadaka, Richard (Frontiers in Psychology, 2022)
Technostress is evolving as an imperative area of academic research amid the “new normal” settings of working remotely. Research has investigated the relationships between technostress and job outcomes and proposed individual-and organizational-level approaches to manage it. However, insights into the influence of dynamic personality differences on this relationship are limited. This study ties the concept of self-efficacy to the transactional model of stress and coping and investigates to what extent computer and social self-efficacy imoderate the relationships between technostress creators and frontline employee’s job performance . Findings shift the focus from the negative aspects of technostress and outcomes to both positive and negative aspects. This study’s contributions and implications for theory and practice are discussed.